Frugal Entrepreneurship: Profiting With Inclusive Growth - Hossain, Mokter (2021)
Frugal entrepreneurship (FE) is increasingly considered an important change-maker in emerging markets, serving the unmet market needs of the poor. However, we lack an understanding of who the protagonists of the FE are, their constraints, drivers, and outcomes. Using an inductive research approach with multiple cases, we build a framework that explains constraints, drivers, and outcomes of the FE. We identify three types of constraints—resource, institutional, and scale-up constraints. FEs’ creation process involves an innovative approach and institutional support as drivers. Unlike conventional firms, the study points out the duality of outcomes of FEs—business growth and inclusive growth. Despite many constraints, FEs demonstrate proven success in providing affordable products for low-income customers and show a way of profiting with inclusive growth. Our article makes several contributions along with both theoretical and practical implications.